HOW TEXT-BASED TEACHING PROMOTE DIMENSIONS OF LITERACY SKILLS IN EFL CLASS - Dwi Winarsih; Sirajul Munir (Ta'dib, 2021)
This case study aimed to reveal how high school teachers in a municipality of Central Java as participants promoted dimension of literacy in text-based teaching in EFL classrooms because they were responsible to equip students with literacy skills in order to be smart and have critical thinking. The data were collected by recording, structured open-ended interviews, and classroom observations. Teachers whose students’ English proficiency belonged to fair tent to promote linguistic dimensions of literacy. They spent most of the teaching session by discussing elements of language such as structure or vocabulary and aims of text as an effort to promote socio cultural dimension. Teachers whose students had a good English proficiency promoted linguistic, socio cultural, cognitive and developmental dimension of literacy. The practical pedagogical implication is that teachers’ awareness of integrated particular teaching methods in the classroom is needed to promote students’ proficiency of literacy dimensions and equip students with 21st literacy skills.